Pengaruh Neuro Muscular Taping (NMT) terhadap Kelenturan Gerak Fleksi Lumbal pada Perawat Bagian Instalasi Gawat Darurat di RSUD Bangil - Setiawan Edi Kriswanto; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective : To find out the affect of NeuroMuscularTaping (NMT) methods in  lower back flexion flexibility. Methods : This study use Quasi Experimental method with one pre and post group with cross sectional intervention. The numbers of the respondent are 29 people with purposive sampling techniques. The data collection techniques use sit and reach test with observation. Normality test use Shapiro Wilk continued with data analysis use Wilcoxon Sign Rank Test. Results : The result of Sit and Reach Measurement of  NeuroMuscularTaping (NMT) intervention post test show that there is a change in lower back flexibility, and the result of the hypothesis with abnormal data distribution show a significant value of <0,000 Conclusion : Neuromuscular Taping (NMT) methods increase the lower back flexibility in flexion motion in nurses who have a dynamic work patterns.